PRINCESSES IN DISCOURSE: THE DISNEY DOLLS CHARACTERS IN CHILDREN'S VISION - Michelle Brugnera Cruz Cechin; Thaise da Silva (Editora da Universidade de Santa Cruz do Sul, 2015)
This study describes a qualitative research held in a school in the public school system of Porto Alegre, Rio Grande do Sul, focusing on the speeches of children about the Disney princesses dolls. The goal is to understand how this group of children addressed the gender identity and cultural differences represented by these characters. The princesses present a model of gender identity and behavior to be followed by children in films, games, books and dolls. When children played around with these dolls, they confirmed, challenged and transformed gender pedagogy taught by these characters, who have taken leadership roles in banter between peers in the classroom. The opportunity to play and reflect on these toys allowed new possibilities of thinking distinct modes of subjectivation.